Fragaria vesca L. Extract: A Promising Cosmetic Ingredient with Antioxidant Properties - Couto, Joana (2020)
Fragaria vesca L. (F. vesca), popularly known as wild strawberry, is a plant from the Rosaceae family, found in temperate and subtropical areas of the northern hemisphere. F. vesca leaves have been shown to have antiseptic, emollient, and dermatological protection properties, due to the presence of bioactive compounds, such as flavonoids, phenolic acids, ellagitannins, and proanthocyanidins. In this study, a F. vesca extract was obtained by an optimized extraction process, and was characterized by HPLC, ROS scavenging activity, cytotoxicity assays in HaCaT cells, and tyrosinase inhibitory activity determination. The most active extract was then incorporated in a hydrogel with hydroxyethylcellulose at 2% (w/w), which was characterized at the physicochemical, stability, cytotoxicity, and ROS scavenging activity levels to evaluate its quality, safety, and efficacy. In vivo studies, human repeat insult patch testing, and an assay to determine their antioxidant efficacy, were also performed. The results showed that the Fragaria vesca extracts had antioxidant activity and that the F. vesca extract-based hydrogel exhibited cutaneous compatibility, acceptability and antioxidant efficacy, being stable, and suitable for topical application.